Crystallographically degenerate B2 precipitation in a plastically deformed fcc-based complex concentrated alloy. Issue 3 (4th March 2018) - Choudhuri, Deep; Shukla, Shivakant; Green, Whitley B.; Gwalani, Bharat; Ageh, Victor; Banerjee, Rajarshi; Mishra, Rajiv S.
ABSTRACT: Bcc -ordered B2 and fcc phases manifest three different orientation relationships (ORs) in the same microstructure: Kurdjumov–Sachs, Nishiyama–Wasserman and Pitsch. This unique microstructure was developed via conventional cold-rolling and subsequent annealing of an fcc -based Al0.3 CoCrFeNi complex concentrated alloy (CCA). The degeneracy in crystallographic ORs was caused by {111}⟨112⟩twins, on multiple {111}, from the prior cold-rolling step. Annealing produced B2 precipitates on all the major fcc slip-systems by heterogeneously nucleating B2 at twin-matrix interfaces and twin–twin intersections. Such a precipitation-hardenable microstructure is expected to increase the strength of fcc -based CCAs by effectively blocking 1/2⟨110⟩and 1/6⟨112⟩mobile dislocations. Impact statement Three different fcc -B2 orientation relationships (ORs) were observed for the first time in complex concentrated alloys. Such degenerate ORs in B2 precipitation can potentially block dislocation on multiple slip planes. GRAPHICAL ABSTRACT: